Real-World Clinical Experience of Rosuvastatin as a Lipid-Lowering Therapy for Primary and Secondary Prevention of Cardiovascular Events (REAL ROSE) - Mehta, Ashwani; Jain, Pradeep; Patil, Ravikant; Sashi Kant, T; Indurkar, Sanjiv A; Kota, Sunil Kumar; Revankar, Santosh; Gupta, Amit (Curēus (Palo Alto, CA), 2022)
Background Rosuvastatin effectively reduces endogenous cholesterol synthesis and low-density lipoprotein (LDL) cholesterol and increases high-density lipoprotein (HDL) cholesterol. This study aimed to evaluate the clinical characteristics of patients and treatment patterns of rosuvastatin as a lipid-lowering therapy for primary and secondary prevention of cardiovascular events in Indian settings. Methods This real-world, retrospective multi-centric observational study included patients aged >18 years who received treatment with a rosuvastatin/rosuvastatin-based combination. Demographic and data about concomitant diseases and medications were recorded. Results Out of 1,816 patients, the majority were men (66.2%); the mean age was 54.1 years. The patients prescribed rosuvastatin for primary and secondary prevention of cardiovascular events were 71.9% and 28.1%, respectively. Rosuvastatin 10 mg (56.8%) was the most commonly prescribed dose. For primary prevention, 10 mg (65.0%) was the most preferred dose, and for secondary prevention, 20 mg (54.3%) was the most preferred dose. Rosuvastatin treatment significantly (pre- vs. post-treatment) reduced the levels of total cholesterol (227.2 vs. 178.4 mg/dL), triglycerides (212.6 vs. 154.4 mg/dL), and LDL cholesterol (167.0 vs. 125.6 mg/dL), and increased HDL cholesterol levels (40.7 vs. 44.3 mg/dL) (p<0.0001). A total of 1,196 patients received combination therapy with rosuvastatin (aspirin, 34.0%, and fenofibrate, 21.9%). Adverse events were reported in 0.4% of the study population (leg pain, nausea, muscle cramps/pain, bleeding, and myalgia). Conclusion This study demonstrated the clinical effectiveness and safety of moderate- to high-intensity rosuvastatin (5-40 mg) for primary and secondary prevention of cardiovascular events in the Indian population. A primary prevention strategy with statins can reduce cardiovascular events and associated morbidity and mortality.